Pengenalan dan Adopsi Teknologi Website Pemasaran Produk Pertanian: Analisis Transformasi Digital pada Kelompok Wanita Tani Kebun Soka Berseri - Anggia Kamila Maharani; Anisa Dwi Ariani; Ega Maulana; Muhammad Fadhlan Restu; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
The Kebun Soka Sari Women Farmers Group in Sukaraja Village is a group that empowers women in agriculture to support food security and the family economy. Its members are housewives around Griya Asoka who manage small farms in their yards. They develop pakcoy cultivation with a hydroponic system. The women farmer group not only provides healthy food, but also adapts to modern agricultural technology. They are active on social media and sell hydroponic pakcoy vegetables to supplement their income. The purpose of this journal is to determine the adoption of digital technology and introduce a website for marketing agricultural products. The research method used is quantitative method by distributing questionnaires. The questionnaire aims to determine the level of knowledge of farm women's groups and the use of digital in product marketing. The use of digital in product marketing in the Women Farmers Group has no difficulty in adopting digital technology. They have used digital applications to share activities and promote products. Their customers come from local residents and outside the village. They are also enthusiastic about the introduction of websites in product marketing.